2015
DOI: 10.3311/ppch.7577
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Various Operating Parameters of Proton Exchange Membrane

Abstract: A three-dimensional computational fluid dynamics in-house

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…More information about the result and discussion of the base model can be referred to Refs. [7,8,15] (Fig. 5b).…”
Section: Numerical and Experimental Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…More information about the result and discussion of the base model can be referred to Refs. [7,8,15] (Fig. 5b).…”
Section: Numerical and Experimental Proceduresmentioning
confidence: 93%
“…Wang et al [14] studied the effect of some main operating parameters such as temperature and humidity on the efficiency of PEMFC, by using pure hydrogen, experimentally. Ahmadi et al [15] accomplished the numerical simulations and experimental tests to investigate about the important operating parameters. In this paper, performance of step-liked gas channels is investigated and observed that this design for channels enhances the efficiency of species transmitting to the reaction regions.…”
Section: Introductionmentioning
confidence: 99%
“…In this numerical simulation, the following dominant equations are operated. The momentum mass conservation and equations of Species are as follow [1]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…The proton membrane fuel cell, a novel future energy source, applying a polymer membrane as electrolyte, has attracted intense attention chiefly for transportation and residential purposes [1]. The current fuel cell carries considerable advantages including; high efficiency, noiselessness and compliance with environmental standards, low temperature operation, fast start up, no liquid electrolyte and simple design [2].…”
Section: Introductionmentioning
confidence: 99%
“…Protonexchange membrane (PEM) fuel cells are a new energy resource for a variety of applications, including transportation. 1 PEM fuel cells have advantages over other fuel cells in the automotive industry, including high efficiency, high power density, high operating temperature, and bio-friendliness. 2 Fuel cells and systems have recently been extensively studied.…”
Section: Introductionmentioning
confidence: 99%